2020
DOI: 10.1177/1742715020902906
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive and maladaptive narcissism, charisma, and leadership performance: A study of perceptions about the presidential leadership of Donald Trump

Abstract: The current study examines the effects of perceptions of leader adaptive and maladaptive narcissism on ratings of charisma and presidential leadership performance for Donald Trump by registered voters. We present a model examining differing dimensions of narcissism, and their effects on attributed charisma and perceptions of leadership performance for Donald Trump. Structural equation modeling results reveal positive effects of adaptive narcissism on attributed charisma and leadership performance of Donald Tru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 73 publications
(163 reference statements)
0
7
0
Order By: Relevance
“…(2) a lack of testing, for example, significant testing started only mid-March 2020; (3) epistemic hubris breeding false assumptions and incompetent actions, for example, Trump suggested that disinfectants or ultraviolet light could be used to kill the virus; and (4) a misinformed and mistaken herd immunity policy, for example, Trump's adviser Scott Atlas advocated a herd immunity strategy (Bell, 2020;De Swielande, 2020;Deegan Krause, 2019;Dixon, 2020;Gaouette et al, 2020;Krmack, 2020;Lacatus, 2020;Lacatus and Meibauer, 2020;Mayer, 2020;Renshon, 2020;Rhodes and Sutton, 2017;Schumaker, 2020;Shear et al, 2020;Stokols and Biermann, 2020;Waldman, 2020;Wehle, 2020;Wehner, 2020;Williams et al, 2018Williams et al, , 2020. On the other hand, New Zealand enacted Covid-19 prevention measures promptly 3 days after the WHO announcement on 30th January of Covid-19 as a public health emergency (e.g.…”
Section: Conducive Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) a lack of testing, for example, significant testing started only mid-March 2020; (3) epistemic hubris breeding false assumptions and incompetent actions, for example, Trump suggested that disinfectants or ultraviolet light could be used to kill the virus; and (4) a misinformed and mistaken herd immunity policy, for example, Trump's adviser Scott Atlas advocated a herd immunity strategy (Bell, 2020;De Swielande, 2020;Deegan Krause, 2019;Dixon, 2020;Gaouette et al, 2020;Krmack, 2020;Lacatus, 2020;Lacatus and Meibauer, 2020;Mayer, 2020;Renshon, 2020;Rhodes and Sutton, 2017;Schumaker, 2020;Shear et al, 2020;Stokols and Biermann, 2020;Waldman, 2020;Wehle, 2020;Wehner, 2020;Williams et al, 2018Williams et al, , 2020. On the other hand, New Zealand enacted Covid-19 prevention measures promptly 3 days after the WHO announcement on 30th January of Covid-19 as a public health emergency (e.g.…”
Section: Conducive Contextmentioning
confidence: 99%
“…Trump’s pandemic leadership was objectively bad: as noted above, the death rate for the United States of America at the time of writing was 2208 persons per million and was the worst amongst English-speaking countries, whilst the death rate for New Zealand was six persons per million (a factor of 368 times lower) and was the lowest death rate for any country (see https://coronavirus.jhu.edu/map.html). The confluence of Trump’s destructive leader behaviours, a conducive context and susceptible followers resulted in: (1) the USA being too late to lockdown, for example, the first case reported in the US was on 20th January, the lockdown was 2 months later; (2) a lack of testing, for example, significant testing started only mid-March 2020; (3) epistemic hubris breeding false assumptions and incompetent actions, for example, Trump suggested that disinfectants or ultraviolet light could be used to kill the virus; and (4) a misinformed and mistaken herd immunity policy, for example, Trump’s adviser Scott Atlas advocated a herd immunity strategy (Bell, 2020; De Swielande, 2020; Deegan Krause, 2019; Dixon, 2020; Gaouette et al, 2020; Krmack, 2020; Lacatus, 2020; Lacatus and Meibauer, 2020; Mayer, 2020; Renshon, 2020; Rhodes and Sutton, 2017; Schumaker, 2020; Shear et al, 2020; Stokols and Biermann, 2020; Waldman, 2020; Wehle, 2020; Wehner, 2020; Williams et al, 2018, 2020). On the other hand, New Zealand enacted Covid-19 prevention measures promptly 3 days after the WHO announcement on 30th January of Covid-19 as a public health emergency (e.g.…”
Section: Background: the Toxic Trianglementioning
confidence: 99%
“…In this study, we explore leader responses to crises that may be perceived as threats by investigating former U.S. President Donald J. Trump, who has been consistently referred to as a narcissistic leader in both the academic literature (Visser et al, 2017; Williams et al, 2020) and popular press (Lunbeck, 2017). Moreover, the unique circumstances of Trump’s first impeachment (i.e., his seeking foreign assistance with a campaign) and the wide criticism of his handling of the COVID-19 pandemic (Jacobson, 2020) present interesting contexts in which to study a narcissistic leader’s charismatic appeal to followers during crises.…”
Section: Introductionmentioning
confidence: 99%
“…Entitlement is activated in response to one’s belief that they were either wronged or unfairly treated (Kimmel and Ferber, 2000; Williams et al, 2020). Earlier psychoanalytic perspectives described entitlement as a defense against shame and guilt by which individuals externalize their self-conscious emotions by directing anger or blame toward others (Bishop and Lane, 2002; Horney, 1950).…”
Section: Introductionmentioning
confidence: 99%